New skills for new jobs: China and the EU - Shared labour market experiences to inform the harmonious and sustainable society of the future (Brussels, 2010)
"This report presents the research findings from a joint China and EU project on New Skills for New Jobs in the context of the crisis and its impact on vulnerable groups.